A study of the association of rs12040273 with susceptibility and severity of coronary artery disease in a Chinese Han population - Bo Yang; Shan Yan; Jianjun Yan; Yafei Li; Mohammad Reeaze Khurwolah; Liansheng Wang; Zhong Chen (BMC Cardiovascular Disorders, 2018)
Abstract Background The single nucleotide polymorphism (SNP) rs12040273, a variant of UDP-N–acetylgalactosamine, polypeptide GalNAc-transferase 2, has recently been reported to be significantly associated with development of carotid artery intima-media thickness (IMT) in a Chinese population based on a genome-wide association study. Because IMT is a potent marker of coronary artery disease (CAD), the aim of this study was to evaluate the relation of rs12040273 to susceptibility and severity of CAD in a Chinese Han population. Methods We performed a hospital-based case-control study. Three hundred and thirty-one individuals (199 CAD patients and 112 non-CAD controls) undergoing coronary angiography were consecutively enrolled in the study. The Gensini score results were used to assess the severity of CAD. The method of polymerase chain reaction-ligase detection reaction (PCR-LDR) was used to distinguish different genotypes at rs12040273. Results The distribution of genotypes at rs12040273 was comparable between CAD patients and non-CAD controls (P > 0.05). The frequencies of the genotypes were also not significantly associated with the risk of CAD and its severity assessed by the Gensini score method, with the OR of 1.38 (95% CI = 0.80–2.40, P = 0.24) and 1.14 (95% CI = 0.69–1.86, P = 0.60) respectively. However, stratified analysis showed that the serum HDL-C levels of subjects with the CC genotype were significantly higher than those with CT/TT genotypes in non-CAD controls (P = 0.002). Conclusion Our results suggest that the rs12040273 variants might not be associated with the susceptibility of CAD or its severity in a Chinese Han population. Moreover, the CC genotype could be associated with elevated serum HDL-C levels.